Desulfurization of Basra Diesel Fuel by Emulsification – Adsorption Processes - Khudhur, Ali G.; Hantosh, Ahmed A.; Omer, Mohammed A. (Journal of Petroleum Research and Studies, 2024)
In this study, the combined emulsification–adsorption processes were employed for the desulfurization of Basra diesel fuel. A high sulfur diesel fuel of 1.4538 wt% from the Basra refinery was oxidized effectively with H2O2 and Acetic acid (AcOH) as a catalyst to reduce sulfur content to 1.0875 wt% before being emulsified. The emulsification desulfurization (EDS) process using Alkyl benzene sulfonate (ABS) as a surfactant was optimized by 20 trails according to Response Surface Methodology (RSM). A 0.83886 wt% was achieved at the following optimum conditions: Surfactant concentration 20 wt.%, temperature 57.56 ᵒC, and homogenization speed 5695 rpm. The adsorptive desulfurization (ADS) process using activated bentonite clay was carried out in a batch system. The RSM was applied to determine the effect of contact time (1-10 hr), clay mass (5- 20 gm/50ml), and temperature (30-100 ᵒC) on the sulfur removal. Results showed that the sulfur content of 0.57 wt% was achieved at the following conditions: adsorption time 7.18 hrs., temperature 53.3 ᵒC, and clay mass 15.24 gm/ 50ml. The achieved sulfur removal efficiency was 23% and 32% for EDS and ADS respectively. The diesel fuel quality was studied by GC and IREX.